Prevalence and Characteristics of Allergic Asthma in a Sample of Dairy Farmers - Stoleski, Sasho; Minov, Jordan; Mijakoski, Dragan; Atanasovska, Aneta; Bislimovska, Dragana; Karadzinska-Bislimovska, Jovanka; Donovski, Kire (Scientific Foundation Spiroski, 2024)
AIM: The objective of the study is to evaluate the prevalence characteristics of allergic asthma in a sample of dairy farmers. METHODS: We performed a cross-sectional study including 83 dairy farmers (mean age: 52.6 ± 8.7 years; mean exposure duration: 23.7 ± 7.6 years) compared to 80 office controls (mean age: 52.7 ± 8.2 years) matched for age, smoking habits, and socioeconomic status. Methods of evaluating examined subjects included a questionnaire on respiratory symptoms in the past 12 months, baseline spirometry and histamine challenge, and skin prick tests to standard inhalant and occupational allergens. RESULTS: The frequency of asthma was non-significantly higher in dairy farmers than in controls (7.2% vs. 5%). The frequency of allergic asthma was non-significantly higher in dairy farmers than in controls (6% vs. 3.8%). The frequency of allergic asthma was significantly higher compared to non-allergic asthma in both groups, while the frequency of subjects with allergic asthma who are sensitized to occupational allergens (wheat, corn, rye, cow hairs, molds) was similar in dairy farmers and controls. The risk of sensitization to occupational allergens was non-significantly higher among dairy farmers with allergic asthma (OR = 1,39 [0,18–12,28] CI 95%), compared to office controls. The risk for asthma development was non-significantly higher in subjects sensitized to occupational allergens compared to those who are not sensitized to them both in dairy farmers (OR = 2.00 [0.11–40.60] CI 95%) and office controls (OR = 3.00 [0.00–197.11] CI 95%). The risk for asthma development was about 4 times higher in subjects with atopy compared to those without atopy among dairy farmers (OR = 4.00 [0.22–104.88] CI 95%), while in office controls was almost identical (OR = 1.00 [0.00–39.77] CI 95%). Having in mind sensitization to certain inhalant allergens, asthma was significantly associated with sensitization to Dermatophagoides pteronyssinus both in dairy farmers (p < 0.01) and office controls (p < 0.05). CONCLUSION: The results suggest that occupational exposure among dairy farmers was associated with a higher prevalence respiratory symptoms, lung function impairment, and allergic asthma development. Study findings also can contribute in the detection of critical points for action, predict asthma development, and indicate the need for reduction of adverse occupational exposures by appropriate preventive measures, use of respiratory protective equipment, and implementation of engineering controls.
Keywords: respiratory symptoms; occupational allergens; farming; questionnaire; job exposure